1996
DOI: 10.1074/jbc.271.21.12669
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tyrosine Residues in the Intracellular Domain of the Growth Hormone Receptor Required for Transcriptional Signaling and Stat5 Activation

Abstract: The binding of growth hormone (GH) to its receptor results in its dimerization followed by activation of Jak2 kinase and tyrosine phosphorylation of the GH receptor itself, as well as Jak2 and the transcription factors Stat1, -3, and -5. In order to study the role of GH receptor tyrosine phosphorylation in intracellular signaling, we constructed GH receptors in which combinations of tyrosines were mutated to phenylalanines. We identified three tyrosine residues at positions 534, 566, and 627 that were required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 40 publications
3
71
0
Order By: Relevance
“…Several analyses of the growth hormone (GH) receptor in B-cell function have demonstrated that the proliferative signaling only requires a membrane proximal part of the receptor and activation of the tyrosine kinase Janus activation kinase 2 and the transcription factors STAT1 and STAT3 (signal transducers and activators of transcription) (25). On the other hand, the action of insulin secretion via the GH receptor requires the distal part of the receptor and activation of calcium uptake and STAT5 (26)(27)(28). Thus, GH (and PRL) may affect insulin secretion and B-cell proliferation via distinct signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Several analyses of the growth hormone (GH) receptor in B-cell function have demonstrated that the proliferative signaling only requires a membrane proximal part of the receptor and activation of the tyrosine kinase Janus activation kinase 2 and the transcription factors STAT1 and STAT3 (signal transducers and activators of transcription) (25). On the other hand, the action of insulin secretion via the GH receptor requires the distal part of the receptor and activation of calcium uptake and STAT5 (26)(27)(28). Thus, GH (and PRL) may affect insulin secretion and B-cell proliferation via distinct signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The current evidence suggests that STAT5 activation by GH requires phosphorylation of speci®c tyrosine residues within the GH receptor, thereby providing a high anity binding site for the SH2 domain in the STAT proteins. Speci®c tyrosines in porcine GH receptor (Y534, Y566 and Y627, equivalent to Y534, Y566 and Y626 in rat GH receptor) have been identi®ed as being required for GH-dependent tyrosyl phosphorylation of STAT5 and transcription of the Spi 2.1 promoter (Hansen et al, 1996;Wang et al, 1996). An additional tyrosine (487) has also been suggested as being required for tyrosyl phosphorylation of STAT5 .…”
Section: Mechanism Of Activation Of Stat Proteins By Ghmentioning
confidence: 99%
“…GH induces the binding of STAT5 proteins to IFNg activated sequence (GAS)-like elements (GLE) in several dierent genes, including the GH-sensitive spi 2.1, Insulin 1 and p450 CYP3A 6 beta-hydroxylase genes (Bergad et al, 1995;Galsgaard et al, 1996;Hansen et al, 1996;Subramanian et al, 1995;. STAT5 mediates GH-dependent transcriptional activation of promoter-reporter constructs containing the STAT5-binding promoter elements of these genes (Bergad et al, 1995;Galsgaard et al, 1996;Hansen et al, 1996;Sotiropoulos et al, 1996;Subramanian et al, 1995;Wood et al, 1995).…”
Section: Activation Of Stat Phosphorylation By Sh2-bbmentioning
confidence: 99%
“…Predicted signal peptides, transmembrane domains, N glycosylation sites, and other conserved residues/subdomains were boxed with the same color used in (a). Functional prolines in the box I motif (Goujon et al 1994) and tyrosines (Hansen et al 1996) are highlighted by gray CCCHHHHHEEEEEEECCCCCCCCCHHHHCCCCCCCCCEEEEEECCCCEEEEHHCHCCECCCCCCCCCEEEEEEEECCCCCCCCCEEEEEEHHHCHEEEEEEEHHCCCCEEEEEEECCCCCCCCCCC 309 309 309 309 309 305 305 305 309 309 309 309 318 310 285 282 285 283 280 282 284 289 285 286 286 287 287 287 287 285 287 294 286 294 291 289 293 293 289 289 291 293 303 310 296 297 297 297 297 183 183 183 183 183 179 179 179 183 183 183 183 192 184 159 156 159 157 154 156 158 163 159 160 160 161 161 161 161 159 161 168 160 168 165 163 167 167 163 163 165 167 177 184 170 171 171 171 171 a approximately 35% identity between GHRs of tetrapods and teleosts), the predicted secondary structures are all strikingly similar (Fig. 6a).…”
Section: Lineage-specific Features Of the Vertebrate Ghr/slrs: From Tmentioning
confidence: 99%